Assume that,
adult = x
child = y
x+2y = 35 (1st equation)
2x+3y = 60 (2nd equation)
x = 35-2y (3rd equation)
Substitute 3 into 2 :
2(35-2y) + 3y =60
70-4y +3y = 60
y = 10
x+2y = 35
x+2(10) =35
x +20 =35
x = 15
One adult = $15
The perfect square monomial and its square root are shown in options 1, 2, and 5.
- A perfect square in mathematics is an expression that factors into two equally valid expressions. A monomial is a single phrase that is made up of the product of positive integer powers of the constants, variables, and constants. Consequently, a monomial that factors into two monomials that are the same is called a perfect square monomial.
- 1) 121, 11
- 11² = 121
- A perfect square monomial and its square root are represented by this equation.
- 2) 4x², 2x
- (2x)² = 4x²
- A perfect square monomial and its square root are represented by this equation.
- 3) 9x²-1, 3x-1
- (3x-1)² = 9x²- 6x +1
- This phrase does not depict a square monomial and its square root in perfect form.
- 4) 25x, 5x
- (5x)² = 25x²
- This phrase does not depict a square monomial and its square root in perfect form.
- 5) 49(x^4), 7x²
- (7x²)² = 49(x^4)
- A perfect square monomial and its square root are represented by this equation.
To learn more about monomial, visit :
brainly.com/question/9183135
#SPJ4
T=the amount of shirts
12t-20-8t=100
12t-8t=120
4t=120
t=30
So they must sell at least 30 shirts to make $100.
A= P(1 + r/n) ^nt
21000=7000(1+0.055/2)^1t
t = 20.52 years
Answer:
Step-by-step explanation:
<u>Find zeros first:</u>
- x² + x - 6 = x² + 3x - 2x - 6 = x(x + 3) - 2(x + 3) = (x - 2)(x + 3)
- x = 2, x = -3, x = 7 (but x ≠ 7 as no division by zero)
<u>We have 4 intervals:</u>
- x ≤ - 3, three negatives, the result is negative or zero
- -3 ≤ x ≤ 2, two negatives and one positive, the result is positive or zero
- 2 ≤ x < 7, two positives and one negative, the result is negative or zero
- x > 7, three positives, the result is positive or zero
<u>The solution is:</u>
Correct choice is A